Community detection in graphs - Britto, Felipe Castro de (2021)
The Stochastic Block Model (SBM), is one of the most famous models of graphs with community structure, due to its facility in simulating several different structures. In this work,an introduction to community detection in the SBM model is made, to different approaches to this detection, and conditions to obtain consistency in the detection of communities. An application of these strategies, or algorithms, is also made to know under which conditions,or regimes, also known as fundamental limits, these algorithms have good results, in simulated graphs with different regimes.